Os sentidos da paixão: um estudo de psicopatologia fundamental - Grosman, Adriana (2007)
This paper intends to explore the ambiguity of the term passion, as lack or as excess, in correlation with love in the relationship mother-child, coming particularly from the autism. Therefore, a broader journey was necessary, that is: on the subject's structuring and its vicissitudes. We began from a clinical case in which a mother, apparently marked by the a-pathy, takes his son and makes the analyst uncomfortable. The maternal failure is, thus, called in question. In what measure does the maternal apathy contribute to take the child to a psychopathology as serious as the autism, impeding him from constituting as a subject? And more: and the opposite? The excess, that is, the passion, would not have consequences? Would not it contribute also to this? Suddenly the clinic itself gives us subsidies to articulate the research. No longer the apathy, but the passion in its excessive and deadly aspect. How understanding two so different aspects of passion ? This way, several strings apparently different are being tied until we reach the conclusion that, between passion and "maternal love", there is an abyss. This research is over or it is interrupted here, when it can only move forward making a deeper study of the female subjectivity question